An assessment of contaminants and benthic condition in the Matagorda Bay system (Texas, USA) - Jasmine J. Caillier; Paul A. Montagna; Marie E. DeLorenzo; Katy W. Chung; Peter B. Key (Environmental Science and Pollution Research, 2026)
The Matagorda Bay system has suffered a long-term decline in benthic abundance, biomass, and diversity since the 1980’s. This study examined sediment contamination to determine if legacy pollutants are degrading sediment quality and are a possible cause for ecosystem degradation. Degradation can be indicated by a decline in benthic integrity (i.e., diversity), decreased survival rates of organisms exposed to sediment, and sediment chemical contaminant concentrations over threshold limits. These methods form the Sediment Quality Triad to assess environmental effects. There were no contaminant concentrations above threshold limits for PCBs or DDTs, but 46% of 24 stations had concentrations over threshold limits, established by sediment quality guidelines, for seven trace elements and one PAH: arsenic (As), cadmium (Cd), mercury (Hg), copper (Cu), lead (Pb), nickel (Ni), and silver (Ag); and dibenzo (a,h) anthracene. Mostly near river mouths, 16 of the 24 stations had moderate to high toxicity, and 17 out of the 24 stations had fair to low diversity. Toxicity was inversely correlated with diversity, but there were no correlations between sediment chemistry and toxicity or benthic metrics. These findings indicate that legacy chemical contamination is not driving estuary-wide degradation of benthic communities The only station where high contamination was linked to high toxicity and low diversity was in the uppermost region of Lavaca Bay close to creek mouths. Low diversity and/or high toxicity was common near river and creek mouths. Because unmeasured pollution could be entering from rivers and creeks, management plans for the watershed and non-point sources could help to protect this ecosystem.